Ultrasonic-Catalyzed Oxidation and Dissolution of Tin Using Hydrogen Peroxide - Dongbin Wang; Tian Wang; Shixing Wang; Hongying Xia; Wenlong Miao; Thiquynhxuan Le; Libo Zhang (Molecules)
The traditional alkaline process used to prepare sodium stannate faces the challenges of high temperature, low utilization rate, and large hydrogen peroxide consumption, which is mainly due to the low oxidation dissolution efficiency of tin. Here, a new process by ultrasonic-enhanced oxidation and dissolution efficiency of tin at room temperature was proposed. The effects of temperature, ultrasonic power, sodium hydroxide concentration, hydrogen peroxide dosage, and ultrasonic time on the oxidation dissolution efficiency of tin were systematically investigated. The results show that the process of ultrasonic-enhanced oxidation dissolution of tin is a new method with high efficiency and low cost. At room temperature, the tin dissolution efficiency was as high as 99.3% under ultrasound, which was 28% higher than that of the conventional method under the same conditions. The introduction of ultrasound promoted the generation of strong oxidizing hydroxyl radicals (·OH) from hydrogen peroxide, significantly improved the surface roughness of the tin sheet from 6.875 μm in the conventional treatment to 34.135 μm in the ultrasonic treatment, and destroyed the passivation layer on the surface of the tin sheet, thereby improving the dissolution efficiency of tin. Compared with conventional tin dissolution conditions, ultrasonic-enhanced oxidation could decrease the reaction temperature by 30 °C, reduce the consumption of sodium hydroxide by 33.3%, and save the consumption of hydrogen peroxide by 15% while achieving the same tin dissolution effect. This new technology provides new ideas for the oxidation and dissolution of this valuable metal.